Analisis Determinan Indeks Harga Saham Pada Perusahaan Yang Terdaftar Pada Jakarta Islamic Index (JII) - Paska Prina Br Bangun; Debbi Chyntia Ovami; Sri Fitria Jayusman (Jurnal Riset AKuntansi dan Bisnis, 2023)
This study aims to examine the effect of macroeconomic variables, market capitalization, and the BI rate on the Jakarta Islamic Index (JII) stock price index. The objects of this study are the Central Bureau of Statistics (www.bps.go.id), Bank Indonesia (www.bi.go.id), Statistics on the Indonesia Stock Exchange (www.idx.co.id and www.ojk.go.id) and ICP obtained from the Directorate General of Oil and Gas (www.migas.esdm.go.id) which was carried out using online media. The sample selection method uses saturated sampling technique, which is a sampling method in which the entire population is used as a research sample. The sample in this study is the period from 2016 - 2019, namely 48 periods. Data processing was carried out with the help of the SPSS 20 for windows computer application program. The results of this study indicate that the variable inflation, the IDR-USD exchange rate, the BI Rate have a negative and significant effect on the Jakarta Islamic Index (JII) stock price index.